Fine-tuning the molecular structure of binaphthalene polyimides for gas separations. (May 2019) - Dujardin, Wouter; Van Goethem, Cédric; Zhang, Zidan; Verbeke, Rhea; Dickmann, Marcel; Egger, Werner; Nies, Erik; Vankelecom, Ivo; Koeckelberghs, Guy
Graphical abstract: Highlights: Investigate link polymer structure with gas separation properties of new polyimides. 5 new binaphthalene monomers and 7 new binaphthalene polyimides were synthesized. Polyimides had similar mixed gas separation performances for CO2 /CH4 and CO2 /N2 . Polyimides showed 3–5 times higher permeability than Matrimid. Membranes were further investigated using WAXS, PALS and by simulation of FVEs. Abstract: A set of new stiff and contorted polyimides were prepared to systematically link polymer structure with gas separation properties. Seven novel bridged binaphthalene polyimides were synthesized for this purpose using commercial dianhydrides pyromellitic dianhydride (PMDA), biphenyl-tetracarboxylic acid dianhydride (BPDA) and 4, 4′-(hexafluoroisopropylidene)diphthalic anhydride (6FDA). From these polyimides, freestanding membranes were prepared and tested on mixed gas CO2 /CH4 and CO2 /N2 separation performance. They were further characterized using WAXS and PALS and through the simulation of their free volume elements (FVEs) and gas separation properties. The binaphthalene polyimides had CO2 /CH4 and CO2 /N2 mixed gas selectivities of respectively 40 and 29 and mixed gas permeabilities of about 20 barrer for both gas mixtures.